2012
DOI: 10.1007/s11274-012-1177-0
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in the intestinal tract of juvenile whiteleg shrimp Litopenaeus vannamei: modulation of the bacterial community

Abstract: Molecular analysis of the 16S rDNA of the intestinal microbiota of whiteleg shrimp Litopenaeus vannamei was examined to investigate the effect of a Bacillus mix (Bacillus endophyticus YC3-b, Bacillus endophyticus C2-2, Bacillus tequilensisYC5-2) and the commercial probiotic (Alibio(®)) on intestinal bacterial communities and resistance to Vibrio infection. PCR and single strain conformation polymorphism (SSCP) analyses were then performed on DNA extracted directly from guts. Injection of shrimp with V. parahae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 28 publications
4
33
1
Order By: Relevance
“…The crustacean digestive tract, including gut, stomach, and hepatopancreas, contains a tolerated and relatively constant number of bacteria (Freese and Schink, 2011;Kostanjsek et al, 2004;Kostanjsek et al, 2002;Li et al, 2007;Luis-Villasenor et al, 2013;Tzuc et al, 2014). As determined by our group (unpublished data), bacterial counts that were colonized in the kuruma shrimp (Marsupenaeus japonicus) digestive tract were about 10 6 /g to 10 7 /g tissue for the intestines and the stomach and 10 4 /g to 10 5 /g tissue for the hepatopancreas (Fig.…”
Section: Presence Of Hemolymph Microbiota Is An Endemic Eventmentioning
confidence: 75%
“…The crustacean digestive tract, including gut, stomach, and hepatopancreas, contains a tolerated and relatively constant number of bacteria (Freese and Schink, 2011;Kostanjsek et al, 2004;Kostanjsek et al, 2002;Li et al, 2007;Luis-Villasenor et al, 2013;Tzuc et al, 2014). As determined by our group (unpublished data), bacterial counts that were colonized in the kuruma shrimp (Marsupenaeus japonicus) digestive tract were about 10 6 /g to 10 7 /g tissue for the intestines and the stomach and 10 4 /g to 10 5 /g tissue for the hepatopancreas (Fig.…”
Section: Presence Of Hemolymph Microbiota Is An Endemic Eventmentioning
confidence: 75%
“…Member in genus Meridianimaribacter was frequently found in both healthy water and shrimp in our previous study using culture-dependent method (Zheng et al, 2016). Meridianimaribacter was also found in the intestinal tract of shrimp after adding probiotics (Luis-Villaseñor et al, 2013). It was reported that Meridianimaribacter was dominant in healthy larviculture water of shrimp (Xue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring potential probiotic strains and evaluating their usage in aquaculture are of great value. Generally, probiotics have been reported to confer beneficial effects in some way, including (a) excluding pathogenic bacteria through the production of inhibitory compounds and bacteriocin or competition for adhesion sites (Balcázar et al, ); (b) stimulating the immune function of the host (Castex, Lemaire, Wabete, & Chim, ; Gullian, Thompson, & Rodriguez, ); (c) increasing the nutrition utilization of the host through the production of digestive enzymes (Liu, Chiu, Ho, & Wang, ); and (d) helping the host improve the balance of its intestinal microbiota (Luis‐Villasenor et al, ). To date, many probiotics, such as Bacillus and Lactobacillus , at doses of 1 × 10 7 CFU/g, 1 × 10 8 CFU/g and 1 × 10 9 CFU/g have been shown to improve the growth performance and immune responses of aquatic animals (Dash et al, ; Gupta, Verma, & Gupta, ; Hao et al, ; Yan, Xia, Yang, Hoseinifar, & Sun, ).…”
Section: Discussionmentioning
confidence: 99%
“…compounds and bacteriocin or competition for adhesion sites(Balcázar et al, 2007); (b) stimulating the immune function of the host(Castex, Lemaire, Wabete, & Chim, 2010;Gullian, Thompson, & Rodriguez, 2004); (c) increasing the nutrition utilization of the host through the production of digestive enzymes(Liu, Chiu, Ho, & Wang, 2009); and (d) helping the host improve the balance of its intestinal microbiota(Luis-Villasenor et al, 2013). To date, many probiotics, such as Bacillus…”
mentioning
confidence: 99%